Challenges to Top-Ranked Private Universities in Poland - Musial-Sadilek, Joanna (International Higher Education, 2013)
Although demographic change seriously threatens private higher education in Poland, part of the sector has means to cope. In contrast to the majority of private institutions, top-ranked private institutions enjoy semi-elite characteristics that shield them, not fully but partly, from negative impact on enrollment.